PERANAN CONTROLLER DALAM PERENCANAAN DAN PENGENDALIAN PENJUALAN PADA PT DUTA MULTI KARYA BATAM - Hendry Jaya (MEASUREMENT : Jurnal Program Studi Akuntansi, 2016)
This study aims to determine the role of the controller in the planning and control of sales at PT Duta Multi Karya. The data used to know issues under discussion and namely qualitative data, while based on sources using primary data and secondary data. The method used  in this research is descriptive method. Which aims to provide a clear picture about the object of  research . The results showed that the planning of sales at PT Duta Multi Karya  with has been running well, where the existing system of internal controls within the company.In this case the Company   Duta Multi Karya  do a controller for controlling the sales and  financial  The method used the company Duta Multi Karya  is using discounts.Keywords: The role of Controller, Plan, Sales Control